Mitochondrial protection restores renal function in swine atherosclerotic renovascular disease - Eirin, Alfonso (Oxford University Press, 2014)
AIMS: The mechanisms responsible for renal injury in atherosclerotic renovascular disease (ARVD) are incompletely understood, and few therapeutic options are available to reverse it. We hypothesized that chronic renal damage involves mitochondrial injury, and that mitochondrial protection would reduce renal fibrosis and dysfunction in ARVD pigs. METHODS AND RESULTS: Domestic pigs were studied after 10 weeks of ARVD or sham, treated for the last 4 weeks with daily subcutaneous injections (5 days/week) of vehicle or Bendavia (0.1 mg/kg), a tetrapeptide that preserves cardiolipin content in the mitochondrial inner membrane. Single-kidney haemodynamics and function were studied using fast-computer tomography, oxygenation using blood oxygen level-dependent magnetic resonance imaging, microvascular architecture, oxidative stress, and fibrosis ex vivo. Cardiolipin content was assessed using mass spectrometry and staining. Renal endothelial function was studied in vivo and ex vivo. In addition, swine renal artery endothelial cells incubated with tert-butyl hydroperoxide were also treated with Bendavia. Stenotic-kidney renal blood flow (RBF) and glomerular filtration rate (GFR) decreased in ARVD + Vehicle compared with normal (318.8 ± 61.0 vs. 553.8 ± 82.8 mL/min and 48.0 ± 4.0 vs. 84.0 ± 3.8 mL/min, respectively) associated with loss of cardiolipin, intra-renal microvascular rarefaction, and hypoxia. Bendavia restored cardiolipin content in ARVD and improved vascular density, oxygenation, RBF (535.1 ± 24.9 mL/min), and GFR (86.6 ± 11.2 mL/min). Oxidative stress and fibrosis were ameliorated, and renovascular endothelial function normalized both in vivo and in vitro. CONCLUSION: Preservation of mitochondrial cardiolipin attenuated swine stenotic-kidney microvascular loss and injury, and improved renal oxygenation, haemodynamics, and function. These observations implicate mitochondrial damage in renal deterioration in chronic experimental ARVD, and position the mitochondria as a central therapeutic target.